Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/8904_2016_24
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Storage Disorders in Nonimmune Hydrops Fetalis (NIHF): An Indian Experience

Abstract: Lysosomal storage disorders (LSD) are rare inherited neurovisceral inborn errors of metabolism which may present as nonimmune hydrops fetalis (NIHF) during pregnancy. Although causes of NIHF are highly diverse, LSDs are one of the underlying causes of NIHF. The aim of this study was to elucidate most frequent causes of LSDs presenting as NIHF in Indian population. Several fetal tissues were investigated for enzymatic diagnosis of LSDs using modified fluorometric assays in the current prospective study carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
1
13
1
Order By: Relevance
“…A higher diagnostic rate (36%) was noticed in our study compared with other studies (Moreno et al, 2013;Sheth et al, 2017;Sudrie-Arnaud et al, 2018;Lord et al, 2019;Sparks et al, 2019Sparks et al, , 2020. One reason was that recurrent fetal hydrops in the study represented a highly selected study group, which indicated that a higher incidence of single-gene disorders and non-genetic reasons contributing to NIHF has been ruled out as much as possible in the study following systematic work-up for NIHF.…”
Section: Discussioncontrasting
confidence: 49%
“…A higher diagnostic rate (36%) was noticed in our study compared with other studies (Moreno et al, 2013;Sheth et al, 2017;Sudrie-Arnaud et al, 2018;Lord et al, 2019;Sparks et al, 2019Sparks et al, , 2020. One reason was that recurrent fetal hydrops in the study represented a highly selected study group, which indicated that a higher incidence of single-gene disorders and non-genetic reasons contributing to NIHF has been ruled out as much as possible in the study following systematic work-up for NIHF.…”
Section: Discussioncontrasting
confidence: 49%
“…Ultimately, three additional cohorts were identified. The largest had 108 fetuses with both NIHF and LSD, followed by a cohort of seven fetuses and another cohort of five fetuses …”
Section: Resultsmentioning
confidence: 99%
“…In a study from India reporting a 10 year experience of 33 cases, LSDs were observed to make up 22% of the etiology [10]. With the advent of newer diagnostic tools like next generation sequencing (NGS), it is possible to diagnose metabolic disorders causing NIH, like inborn errors of metabolism (IEM), which previously remained underdiagnosed.…”
Section: Discussionmentioning
confidence: 99%